A Robust Adaptive Filtering Algorithm Against Impulsive Noise - Vega, L. R.; Rey, H.; Benesty, J.; Tressens, S. (2007 IEEE International Conference on Acoustics, Speech and Signal Processing - ICASSP '07, 2007)
A new framework for designing robust adaptive filters is introduced. It is based on the optimization of a certain cost function subject to a time-dependent constraint on the norm of the filter update. Particularly, we will derive a robust variable step-size NLMS algorithm which optimizes the square norm of the a posteriori error subject to the constraint on the norm of the filter change. We also show the link between the proposed algorithm and another one derived using a robust statistics approach. The algorithm is then tested in different environments for system identification and acoustic echo cancelation applications.